The role of gaze and prior knowledge on allocentric coding of reach targets - Lu, Zijian; Klinghammer, Mathias; Fiehler, Katja; Justus Liebig University Giessen (My University, 2018)
In this study, we investigated the influence of gaze and prior knowledge about the reach target on the use of allocentric information for memory-guided reaching. Participants viewed a breakfast scene with five objects in the background and six objects on the table. Table objects served as potential reach targets. Participants first encoded the scene and, after a short delay, a test scene was presented with one table object missing and one, three, or five table objects horizontally shifted in the same direction. Participants performed a memory-guided reaching movement toward the position of the missing object on a blank screen. In order to examine the influence of gaze, participants either freely moved their gaze (free-view) or kept gaze at a fixation point (fixation) throughout the trial. The effect of prior knowledge was investigated by informing participants about the reach target either before (preview) or after (nonpreview) scene encoding. Our results demonstrate that humans use allocentric information for reaching even if a stable retinal reference is available. However, allocentric coding of reach targets is stronger when gaze is free and prior knowledge about the reach target is missing.
Keywords: ddc:150